1996
DOI: 10.1017/s1014233900000626
|View full text |Cite
|
Sign up to set email alerts
|

Bhadawari Buffaloes in India

Abstract: SUMMARYBhadawari buffaloes are reputed for high milk fat and are found in the Agra & Etawah districts of Uttar Pradesh and the Bhind & Morena districts of Madhya Pradesh. Information on the status, management practices, morphological characteristics, body measurements and performance of the Bhadawari breed were recorded from its breeding tract. Animals true to the breed are copper in colour and have a white ring on the lower side of the neck. The population of this breed is declining at a fast pace and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
2
1
3
Order By: Relevance
“…Lactation milk yield of cattle and buffaloes up to 305 days of lactation is the criterion commonly used for the selection of dairy animals and a study of the performance of this trait is of paramount importance for carrying out selection. The overall 305 days milk yield (1213.5 kg) obtained for buffaloes in this study was comparatively higher than the values reported earlier [9][10][11] for Bhadawari buffaloes. The overall lactation milk yield of 1250.5 kg in a lactation of 291.4 days was recorded in the present study.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Lactation milk yield of cattle and buffaloes up to 305 days of lactation is the criterion commonly used for the selection of dairy animals and a study of the performance of this trait is of paramount importance for carrying out selection. The overall 305 days milk yield (1213.5 kg) obtained for buffaloes in this study was comparatively higher than the values reported earlier [9][10][11] for Bhadawari buffaloes. The overall lactation milk yield of 1250.5 kg in a lactation of 291.4 days was recorded in the present study.…”
Section: Discussioncontrasting
confidence: 85%
“…The average service period (172.4 days) observed in the present study was lower than the service period reported by Sharma and Singh [25], Pundir et al [9], Nivsarkar et al [26] and Moioli and Borghese [10] for Bhadawari buffaloes . Average calving interval (522.1 days) recorded here was almost similar to the calving interval (524.7 days) reported by Pundir et al, [9] and higher than the reports of Nivsarkar et al, [26] and Moioli and Borghese [10]. Average dry period of 241.80 days observed in the present study was lower than the reported by Moioli and Borghese (2005) and higher than those reported by Nivsarkar et al, [26] in Bhadawari buffaloes.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Nivsarkar et al (2000) (Mishra et al 2009); mean values of CG, HBD and TL of Murrah were higher than Banni buffalo whereas average values of HL, HW and BL were smaller. BL and W H of grade Murrah were similar to Bhadawari buffalo (Pundir et al 1996). Similarly, the mean values of CG, PG, HL, HW, EL, HBD, PBD and TL of grade Murrah were similar to Gojri buffalo (Vohra et al 2015).…”
Section: Resultssupporting
confidence: 55%
“…From the 1970s a weak undercurrent nudged the conservation or preservation of native breeds but this mainly flowed in the richer and developed countries via, for example the Rare Breeds Survival Trust in the UK (Alderson 1990) and the American Livestock Breeds Conservancy in the USA (Sponenberg and Bixby 2007). There was later interest -much of it of an academic nature -in the developing countries in conservation of indigenous livestock (Burfening and Juan Chavez 1996;Pundir et al 1996;Mpofu 1996;Rege 1999). These types of domestic animal have now come to be known as "animal genetic resources" and have been dignified with the catchy acronym, AnGR (see, for example, FAO 2007).…”
Section: Introductionmentioning
confidence: 99%